The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1097/01.prs.0000472274.92050.67
|View full text |Cite
|
Sign up to set email alerts
|

Higher Dosages of BMP-2 in Alveolar Cleft Repair Result in Higher Rates of Postoperative Nasal Stenosis

Abstract: PLASTIC SURGERY 2015, Abstract Supplement 4 Figure 1. Mean density of iliac bone grafts and BMP/DBM grafts at 6-9 months were identical: 1.38 g/cc (SD: 0.28). A one tailed ANOVA test comparing means showed no statistical significance (p=0.999).Figure 2. At 6-9 months, patients with BMP/DBM grafts had an average of 31.6% bone fill (95% CI: 24.2-38.5%) vs. 32.5% (95% CI: 22.1-42.9%) in the iliac bone population. No difference between means (p= 0.836). CONCLUSIONS:Here we demonstrate that BMP/DBM is equivalent at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Several studies have shown successful rhBMP-2induced bone formation in the craniofacial skeleton [5][6][7]. However, in spite of some exciting data from these human reports, major complications, adverse events, and reoperations have increasingly been attributed to the "off-label" use of rhBMP-2 in spine surgery, including heterotopic ossifica-tion, osteolysis, increased neurological deficits, and cancer, [9,10,24,25] and for maxillofacial surgery, Neovius et al and Goss et al reported severe swelling, while high rates of postoperative nasal stenosis were described in cleft children [8,11]. Because of this, a second FDA warning was issued against the use of this product in the pediatric population out of concern for insufficient data to demonstrate longterm efficacy or safety in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown successful rhBMP-2induced bone formation in the craniofacial skeleton [5][6][7]. However, in spite of some exciting data from these human reports, major complications, adverse events, and reoperations have increasingly been attributed to the "off-label" use of rhBMP-2 in spine surgery, including heterotopic ossifica-tion, osteolysis, increased neurological deficits, and cancer, [9,10,24,25] and for maxillofacial surgery, Neovius et al and Goss et al reported severe swelling, while high rates of postoperative nasal stenosis were described in cleft children [8,11]. Because of this, a second FDA warning was issued against the use of this product in the pediatric population out of concern for insufficient data to demonstrate longterm efficacy or safety in children.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of bioactivity, biomechanical weaknes, and susceptibility to infection are still detrimental to the use of most of them; [3] and even for bone morphogenetic proteins, recently suggested as an effective alternative [4][5][6][7], significant restraints concerning high costs and severe adverse events have emerged [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the lengthy operative time and stay in the hospital, there is a risk of intraoperative blood loss, postoperative pain, and high cost [ 19 ]. On the other hand, rhBMP-2 adverse effects involved severe swelling in maxillofacial surgery and postoperative nasal stenosis in cleft children [ 29 - 30 ]. As a result, the Food and Drug Administration (FDA) warning was issued against the utilization of it in the pediatric population due to a lack of evidence that confirms long-term effectiveness or safety in children [ 19 ].…”
Section: Reviewmentioning
confidence: 99%